Treatment of Diabetes in the Mouse Model by Delphinidin and Cyanidin Hydrochloride in Free and Liposomal Forms - Gharib, Amir; Faezizadeh, Zohreh; Godarzee, Masoud (Planta Medica, 2013)
Cyanidin and delphinidin are the main phenolic antioxidants in the grape (Vitis vinifera). The aim of this study was to investigate the in vitro and in vivo inhibitory effects of delphinidin and cyanidin chloride in the free and liposomal forms on the albumin glycation reaction. Delphinidin and cyanidin chlorides were encapsulated in the liposomes using an extrusion method. The rate of albumin glycation was evaluated using the ELISA method. Finally, in vivo anti-glycation of delphinidin and cyanidin chloride in the free and liposomal forms in diabetic mice was investigated. The encapsulation efficacies of delphinidin and cyanidin chloride in the liposomes were 89.05 % ± 0.18 and 85.00 % ± 0.15, respectively. In vitro treatment with 100 mg/mL delphinidin and cyanidin chloride in free forms could reduce the rate of albumin glycation to 30.50 ± 3.46 and 46.00 ± 2.50 %, respectively. Under identical conditions, the delphinidin and cyanidin chloride-loaded liposomes could reduce the rate of albumin glycation to 8.50 ± 2.10 and 14.60 ± 3.60 %, respectively. In vivo testing showed that anti-glycation activity of delphinidin and cyanidin in loaded forms was higher than in free forms. The daily administration of 100 mg/kg delphinidin chloride-loaded liposomes to diabetic mice at eight weeks could decrease the rate of albumin and HbA1c glycation to 46.35 ± 1.20 and 3.60 ± 0.25 %, respectively. Moreover, under identical conditions, the loaded liposomes with cyanidin chloride could decrease the rate of albumin and HbA1c glycation to 55.56 ± 1.32 and 4.95 ± 0.20 %, respectively. The findings showed that delphinidin and cyanidin chloride, in particular in the liposomal forms, could be used for treatment of diabetes mellitus complications.
Keywords: Vitis vinifera; Vitaceae; albumin glycation; cyanidin chloride; delphinidin chloride; liposome